2013
DOI: 10.1016/j.jacc.2013.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Recovery of Objective Abnormal Cerebral Perfusion With Neurocognitive Improvement After Carotid Revascularization

Abstract: Successful CS for severe carotid stenosis/occlusion improves NCF, but only in patients with objective baseline abnormal cerebral perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
2
24
0
5
Order By: Relevance
“…It appears that carotid revascularization is beneficial for some patients while others do not seem to benefit from it in the long term. Previous research showed that the cognitive improvements that small groups of patients gain from revascularization seem associated with the recovery of abnormal cerebral perfusion (Huang et al, 2013;Yamashita et al, 2012). Cognitive deterioration has, on the contrary, been linked to postoperative hyperperfusion (Chida et al, 2009;Hirooka et al, 2008).…”
Section: Outcome After Carotid Revascularizationmentioning
confidence: 99%
“…It appears that carotid revascularization is beneficial for some patients while others do not seem to benefit from it in the long term. Previous research showed that the cognitive improvements that small groups of patients gain from revascularization seem associated with the recovery of abnormal cerebral perfusion (Huang et al, 2013;Yamashita et al, 2012). Cognitive deterioration has, on the contrary, been linked to postoperative hyperperfusion (Chida et al, 2009;Hirooka et al, 2008).…”
Section: Outcome After Carotid Revascularizationmentioning
confidence: 99%
“…В литературе [18,[20][21][22] документированы слу-чаи регресса неврологического дефицита и улучше-ния реабилитационного прогноза после восстанов-ления мозгового кровотока в функционально зна-чимых областях головного мозга. Значительную роль при этом может играть хирургическая реваску-ляризация головного мозга, приводящая к восста-новлению параметров церебральной перфузии в от-даленном послеоперационном периоде (более 6 мес после операции) [23].…”
Section: Discussionunclassified
“…Neuropsychological abnormalities are closely associated with LA disease (Grau-Olivares et al 2007). Thus, CAS may improve neuropsychological abnormalities of LA patients by carotid revascularization (Huang et al 2013).…”
Section: Discussionmentioning
confidence: 99%